On the Evolution and Problems of Defining General Pedagogy in Pedagogical Lexicography - Bogusław Śliwerski (Nauki o Wychowaniu, 2025)
The article addresses the issue of the evolution of the status of pedagogy in the Polish context. Historically, the boundaries between general pedagogy and its subdisciplines, such as the theory of education, have become blurred, reflecting changes in research dynamics and socio-political transformations. After 1989, discussions on the identity and methodology of general pedagogy were replaced by broader debates on the identity of pedagogy as a discipline. The article highlights the challenges in analyzing contemporary and historical literature on general pedagogy, particularly in the context of hidden ideological influences or undisclosed worldviews of authors. General pedagogy, as a foundation for empirical and theoretical research, is aimed at understanding education. This knowledge contributes to identifying the relationship between scientific and everyday conceptualizations of education, especially in the context of systemic transformation and cultural changes. It thus calls for the revision and enhancement of the framework of general pedagogy to address contemporary challenges and developmental barriers effectively.